The Philosophy in Christianity - Vesey, Godfrey Norman Agmondisham (New York : Cambridge University Press, 1989)
"This important collection examines the central doctrines of Christianity and the ways in which, in the formulation of these doctrines, Christians have drawn on philosophical ideas. What Platonist philosophy lies behind the doctrines of the Incarnation, and of the Trinity? Is this philosophy still part of our world-view, outside the Christian religion? Can Freudian psychology, rather than ancient philosophy, help us to understand how Christ was both divine and human? Is the philosophers' view of God, as omnipotent, compatible with human freedom? According to the scriptural view, is God vulnerable to what we do? Should we not try to know too much about God? Are the truths of religion quite different from those of philosophy, as the Averroists claimed? What is the place of the will in religious belief? Is Wittgenstein a twentieth-century Averroist? These are some of the questions explored in this stimulating and challenging volume. It will have broad appeal among philosophers and theologians, and their students." --
Foreword / Godfrey Vesey -- Logos and trinity : patterns of Platonist influence on early Christianity / John Dillon -- Reason in mystery / Norman Kretzmann -- The philosophy in Christianity : Arius and Athanasius / Maurice Wiles -- Could God become man? / Richard Swinburne -- Augustine's philosophy of being / Christopher Stead -- Predestination and freedom in Augustine's ethics / Gerard O'Daly -- God as creator / Keith Ward -- Foreknowledge and vulnerability of God / J.R. Lucas -- On not knowing too much about God / A.H. Armstrong -- "Where two are to become one" : mysticism and monism / Grace Jantzen -- Faith and godness / Eleonore Stump -- Hope / Stewart Sutherland -- Christian averroism, fideism and the "two-fold truth" / Stuart Brown -- Does philosophy "leave everything as it is"? : even theology? / Renford Bambrough.
"Supplement to Philosophy 1989."
Includes bibliographical references.
Keywords: Philosophy and religion -- History of doctrines; Christianity -- Philosophy -- History of doctrines; Christian theology -- Influence of European philosophy